The Readymade Boomerang : Certain Relations in 20th Century Art : The Eighth Biennale of Sydney. - Block, René; Cooke, Lynne; Murphy, Bernice; Freybourg, Anne Marie; Higgins, Dick; Art Gallery of New South Wales, Sydney (Sydney : Biennale of Sydney, 1990)
Adams, Dennis ; Bajic, Mrdan ; Beuys, Joseph ; Billgren, Ernst ; Bloom, Barbara ; Boltanski, Christian ; Broodthaers, Marcel ; Byars, James Lee ; Cadieux, Geneviève ; Cage, John ; Cragg, Tony ; Darboven, Hanne ; Duchamp, Marcel ; van Elk, Ger ; Fahlström, Oyvind ; Fischli, Peter ; Goldstein, Zvi ; Haacke, Hans ; Hamilton, Richard ; Iglesias, Christina ; Jaar, Alfredo ; Kabakov, Ilya ; Lafontaine, Marie-Jo ; Maciunas, George ; Opie, Julian ; Panamarenko ; Racine, Rober ; Sarkis ; Takalo-Eskola, Vautier, Ben ; etc.
The Readymade Boomerang : Certain Relations in 20th Century Art : The Eighth Biennale of Sydney, Art Gallery of New South Wales, Sydney, 11 April - 3 June 1990
English
kunstcatalogus